1987
DOI: 10.1095/biolreprod36.4.871
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of Gonadotropic Hormone Secretion in Neonatal Pigs

Abstract: The effect of castration and of administration of charcoal-treated porcine follicular fluid (pFF) containing inhibin-like activity on plasma concentration of gonadotropic hormones was studied in neonatal pigs. Plasma follicle-stimulating hormone (FSH) concentration averaged 25.1 +/- 1.5 ng/ml (mean +/- SEM) in 1-wk-old females and gradually declined to 20.2 +/- 0.7 ng/ml 6 wk later. Ovariectomy did not significantly influence plasma FSH concentration. In males, concentration averaged 8.0 +/- 0.7 ng/ml before c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…An increase in plasma FSH after unilateral castration on Day 1 or 10 supports previously reported negative feedback regulation of FSH secretion [41]. This differs from ineffective negative feedback regulation of LH secretion during this period [41][42][43].…”
Section: Discussionsupporting
confidence: 87%
“…An increase in plasma FSH after unilateral castration on Day 1 or 10 supports previously reported negative feedback regulation of FSH secretion [41]. This differs from ineffective negative feedback regulation of LH secretion during this period [41][42][43].…”
Section: Discussionsupporting
confidence: 87%
“…tion. During early postnatal development in gilts, negative feedback regulation of FSH secretion remains inoperative (Colenbrander et al, 1987). These investigators observed similar plasma FSH concentrations in 42-dold gilts whether gilts were intact or had undergone ovariectomy 5 wk earlier.…”
Section: Discussionmentioning
confidence: 84%
“…Concentrations of FSH are high in prepubertal gilts due to ineffective negative feedback mechanisms (Colenbrander et al, 1987). As puberty approaches, plasma FSH decreases (Diekman et al, 1983;Camous et al, 1985) in association with the appearance of antral ovarian follicles (Oxender et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of an LH response to NAL and morphine (Trudeau et al 1988) (Colenbrander et al 1978;Trudeau et al 1988) in 4-to 5-wk-old boars is not conducive to opiodergic control of LH secretion (Bhanot and Wilkinson 1984 (Colenbrander et al 1987). In contrast, injection of GnRH in 4-to 6-wk-old male pigs stimulates release of both gonadotropins (Trudeau et al 1988 and present study We appreciated the help of Ed Maycher, Bob…”
mentioning
confidence: 67%